2016
DOI: 10.1371/journal.pntd.0004798
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Ocular Chlamydia trachomatis Infection and Active Trachoma in the Western Division of Fiji

Abstract: BackgroundTrachoma is the leading infectious cause of blindness and is caused by ocular infection with the bacterium Chlamydia trachomatis (Ct). While the majority of the global disease burden is found in sub-Saharan Africa, the Western Pacific Region has been identified as trachoma endemic. Population surveys carried out throughout Fiji have shown an abundance of both clinically active trachoma and trachomatous trichiasis in all divisions. This finding is at odds with the clinical experience of local healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…In a previous study in the Western Division of Fiji we reported a trachomatous inflammation – follicular (TF) prevalence of 2.8% and an ocular chlamydia infection prevalence of 2.3%. 2 These serology data are comparable to other settings where there is a low prevalence of both TF and ocular chlamydia infection. 21 Steeply increasing age-specific anti-pgp3 prevalence in children aged between 1 and 10 years is thought to be indicative of intense transmission of ocular C. trachomatis ; in this population the prevalence of anti-pgp3 antibodies was already high in the 1-year age group, suggesting the majority of seropositivity was acquired at in the first year of life.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…In a previous study in the Western Division of Fiji we reported a trachomatous inflammation – follicular (TF) prevalence of 2.8% and an ocular chlamydia infection prevalence of 2.3%. 2 These serology data are comparable to other settings where there is a low prevalence of both TF and ocular chlamydia infection. 21 Steeply increasing age-specific anti-pgp3 prevalence in children aged between 1 and 10 years is thought to be indicative of intense transmission of ocular C. trachomatis ; in this population the prevalence of anti-pgp3 antibodies was already high in the 1-year age group, suggesting the majority of seropositivity was acquired at in the first year of life.…”
Section: Discussionsupporting
confidence: 72%
“…2 No mass distribution of azithromycin for trachoma or yaws has previously been carried out in this region, nor any recent penicillin-based mass treatment campaigns for yaws, to the best of the authors’ knowledge. Data are reported in line with the STROBE guidelines for cross-sectional surveys (Supplementary File 1).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Samples were tested for Homo sapiens ribonuclease subunit (RPP30; endogenous control) and open reading frame 2 of the Ct plasmid (diagnostic target) using a previously evaluated droplet digital PCR assay 20 with minor modifications 21 .…”
Section: Methodsmentioning
confidence: 99%